The Effect Of The Teacher’s Feedback Approach Towards Students’ Descrptive Writing Skill At Grade Tenth Of SMK Bhakti Utama Bandar Lampung - Nila Kurnijanti (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
A teacher needs to give motivation to the students to increase their writing quality. The teacher should be a good guide for the students by giving a good feedback when they improve their knowledge in writing.This research is to study the effect of the teacher’s feedback approach towards students’ descriptive writing skill. Most of the teachers believe that providing students with effective feedback on their writing is vital as it helps students to correct their own mistakes and be more independent writers, which will in turn train them to become better writers [5].This research was conducted to two group design, which represented of tenth grade students of SMK Bhakti Utama Bandar Lampung. The group was selected with Cluster Sampling Technique. There are 20 students in experimental and control class. The data were collected with a pre-test, treatment and post-test. Then, they were analyzed with t-Test for two group design.Based on the result of calculation, It can be seen that the students’ ability in writing descriptive text in the experimental group after the treatment is significant, p 1% is 2,71, p 5% is 2,02 and the t value is 4,11. It means that the p value is smaller than the t value. It is found that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The students’ ability in writing descriptive text is taught by using teacher’s feedback is more effective than writing descriptive text using traditional method. So, there is effect of the teacher’s feedback approach towards students’ ability in writing descriptive text.